THE STRENGTH OF EVIDENCE OF RECONSTRUCTION (RE-RECONSTRUCTION) CARRIED OUT BY INVESTIGATORS IN CRIMINAL CASES - Cut Nurita; Muhammad Ridwan Lubis; Muhammad Ansori Lubis; Syawal Amry Siregar (Jurnal Ilmiah METADATA, 2026)
Reconstruction plays a crucial role in criminal evidence, specifically to clarify and illustrate the occurrence of a crime by reenacting how the suspect committed the crime, thereby further convincing the investigator of the truth of the suspect's or witness's testimony. Reconstruction is used to obtain a picture of the criminal incident committed by the suspect and to reconcile the statements of the suspect and witnesses, thus clarifying the crime. The evidentiary power of the reconstruction (re-enactment) conducted by investigators during the investigation of a crime lies in the reconstruction's results, as evidence from the suspect/defendant outside of court. If it is consistent with other evidence, it will serve as a tool for finding evidence or clues in court.